A tisket a tasket what happened to Market Basket?. Issue 3 (12th September 2016) - Bosco, Susan; Harvey, Diane M.
Abstract : Synopsis: The saga of Market Basket took place over a period of months during which a significant upheaval occurred in the long-successful business. The turmoil drew in a broad range of stakeholders. In a rare chain of events, non-unionized workers and managers engineered a change in senior management of the company. Their willingness to sacrifice their livelihoods in support of one person exemplifies the impact that can be made by a single, authentic, leader. This case draws upon secondary sources which provide insight into broad panoply of business and organizational behavior issues. The primary focus of the case, however, is leadership. Research methodology: This case was developed using secondary sources and court documents that reported on the events that precipitated the problems at Market Basket as well as the strike and aftermath. Relevant courses and levels: Management principles, organizational behavior. All undergraduate class levels would be appropriate. Theoretical bases: This case exemplifies these three major theories in a real-life situation: stakeholder theory, corporate culture theory, organizational commitment.